Representation Of Poverty In Kompas Daily’s “Suara Tak Terdengar” Series On Social Media - Adi Prinantyo; Nurul Hasfi; Kristiyawanto Kristiyawanto (Master of Communication Science Program, Universitas Diponegoro, 2026)
Reporting on poverty has always been a compelling topic for the mass media. Beyond its news value, such reporting reflects the media’s ideal role as an institution that exercises social control over those responsible for tackling poverty, particularly the government and the state. Kompas is one of Indonesia’s major mass media outlets, which, to this day, continues to demonstrate a commitment to highlighting the issue of poverty as part of its social control function. Using the netnography research method, this study examines two issues: the narratives of poverty presented by Kompas and the ideology underpinning them, as well as the audience’s response to such coverage. The subject of this study comprises Kompas’s posts on X (Twitter), Instagram and Facebook regarding the “Suara Tak Terdengar” (Unheard Voices) reporting programme throughout 2024. The findings indicate that Kompas has successfully raised the issue of poverty on social media, attracting the audience’s attention, although there are still limitations in engagement on certain issues. This article also demonstrates that the issue of poverty can still be addressed whilst upholding humanitarian principles and simultaneously serving as a tool for state control. These findings also distinguish this study from previous research, which suggested that coverage of poverty on social media tends to focus on individual cases and is prone to reinforcing negative stereotypes of the poor.